USO E INFLUENCIA DE LA INFORMACIÓN EN PROCESOS ESTRATÉGICOS: ESTUDIO EXPLORATORIO EN UNA UNIVERSIDAD MEXICANA - Julio César López Díaz; Ana María de Guadalupe Arras Vota; Juan Manuel Soto Parra (European Scientific Journal, ESJ, 2014)
The information is considered a strategic asset for institutions of higher education. Since 1980, it has been argued that Mexican universities have had difficulties in improving strategic management processes; collection and usage of information for decision making have been pointed out as causal factors. The objective of this study was to evaluate the use and influence of information in strategic processes in an institution of higher education in Mexico. A case study, exploratory and descriptive-comparative, was conducted in which four groups were integrated to perform controlled strategic processes. Three groups received explicit information: quantitative, qualitative, or combined (quantitative + qualitative); the fourth group did not receive information whatsoever. Groups' conversations were recorded, transcribed and analyzed by means of the software HyperRESEARCH and the statistical program SAS. The results suggest that the type of information influenced on the behavior and characteristics of the strategic processes.